1989
DOI: 10.1099/0022-1317-70-10-2637
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Cotton Rats against Human Respiratory Syncytial Virus by Vaccination with a Novel Chimeric FG Glycoprotein

Abstract: SUMMARYThe cotton rat model of experimental human respiratory syncytial virus (RSV) infection was used to study the efficacy of FG, a novel chimeric glycoprotein which was expressed in insect cells using a baculovirus vector. FG contained the extracellular regions of the F (fusion) and G (attachment) glycoproteins of RSV. Vaccination with FG resulted in induction of neutralizing antibody and was correlated with protection of lung tissue from RSV challenge against both serogroup A and B virus strains. Both crud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…For this latter analysis, most studies used recombinant viruses expressing the F protein. It has been well demonstrated that vaccination with such protein results in the induction of neutralizing antibodies and a significant reduction in the titre of RS virus in lung tissue after challenge (Brideau et al, 1989;Olmsted et al, 1986;Stott et al, 1987;Wertz et al, 1987). The results reported here show that defined synthetic peptides also induce neutralizing antibodies and could be used as an alternative in selectively exploring the immunogenicity of the F protein.…”
Section: Discussionsupporting
confidence: 52%
“…For this latter analysis, most studies used recombinant viruses expressing the F protein. It has been well demonstrated that vaccination with such protein results in the induction of neutralizing antibodies and a significant reduction in the titre of RS virus in lung tissue after challenge (Brideau et al, 1989;Olmsted et al, 1986;Stott et al, 1987;Wertz et al, 1987). The results reported here show that defined synthetic peptides also induce neutralizing antibodies and could be used as an alternative in selectively exploring the immunogenicity of the F protein.…”
Section: Discussionsupporting
confidence: 52%
“…2) suggest FHN-vaccinated animals are responding to both the F and HN portions. In our previous work using the FG chimeric glycoprotein for control of RSV infection, we had shown that the majority of the anti-FG antibody response was to the F portion of FG (Brideau et al, 1989). Host response to more than one major viral glycoprotein target may be needed to control paramyxovirus infections effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Lysates and individual glycoproteins were preadsorbed to microtitre plates prior to assay. The assay was performed as previously described (Brideau et al, 1989). ELISA titres were expressed as the reciprocal of the dilution of sera giving 50 % of the maximum binding activity.…”
Section: Vaccinations Preparations Of Glycoproteins Adsorbed To Alummentioning
confidence: 99%
See 2 more Smart Citations